Field monitoring of urban thermal comfort parameters in various street canyons - Luk, Zhen Hao (2018)
With the expansion of concrete surfaces in developing countries, the urban areas around the countries show a significant increase in temperature compared to that of rural areas. This phenomenon is called the Urban Heat Island [UHI] effect. The purpose of this study is to assess outdoor thermal comfort parameters under various street geometry and orientations as well as surface reflectance characteristics. This requires on-site monitoring and field data collection of urban thermal comfort parameters as well as building thermal characteristics required for calibrating numerical models. Using this data, urban areas are simulated through software to understand how buildings absorb/emits heat at different times of the day.